Interaction of Acanthamoeba T5 with a Vero Cell Culture: An Exploratory Study Using Live-Cell Imaging and Confocal Microscopy - Elizabeth Abrahams-Sandi; Mónica Prado-Porras; Johan Alvarado-Ocampo; Jacob Lorenzo-Morales; Lissette Retana-Moreira (Microorganisms)
Acanthamoeba is a free-living amoeba widely distributed in nature, responsible for clinical cases of encephalitis and keratitis in humans. Due to the increase in the number of cases in recent years, understanding the damage mechanisms employed by the amoeba is very important for the clinical management of the disease, development of diagnostic tools and identification of therapeutic targets. To date, most experimental studies to determine the virulence factors and pathogenesis of Acanthamoeba have employed genotype T4 as an infection model, resulting in minimal information regarding other genotypes. In this work, we explored the direct and indirect effect of A. lenticulata genotype T5 trophozoites and their excretion/secretion products over a Vero cell monolayer. Using confocal and real-time microscopy, we witnessed a significant direct mechanical action of the trophozoites on the cells during the adhesion stage. Additionally, we observed the formation of digitiform phagocytic structures through which the nuclear material of the target cell appears to be specifically sucked by the amoeba without the involvement of any lytic mechanism. Moreover, an increase in lysosomal activity in the cytoplasm of trophozoites of Acanthamoeba, and the effect of the excretion/secretion products on the actin filaments of the target cells were observed during the first 2–3 h post-infection.